A CHECKLIST OF THE HERRINGS (ORDER: CLUPEIFORMES) IN THE VIETNAMESE MARINE WATERS - Thao, Le Thi Thu; Quang, Vo Van (Vietnam Journal of Marine Science and Technology, 2014)
The synonym fish names, which have not checked in when using scientific names and referring at several publications, is negatively impacted on name definition and classification of fishes. Therefore, the paper aims to provide scientific names of the herrings in the Vietnamese marine waters completely and exactly. Nowadays, two families Clupeidae and Engraulidae (order Clupeiformes) are first in fishing production in the world, in which genera Stolephorus and Encrasicholina are in the top ten fish groups that have high production in the Southeast Asia water. They are widely distributed from North to South in Vietnam. Beside they also are exported objects and have high economic value. Forty one documents published during 1964-2012 listed 266 species names belonging to 53 genera and 16 families of the order Clupeiformes in different ecological marine waters in Vietnam. This study corrected, updated and confirmed the species composition of the herrings in the Vietnamese marine waters with 95 species belonging to 30 genera and 4 families. The results play important roles of biodiversity assessment and marine fish protection.